Shield of Protection (novella). - Mentink, Dana; Mills & Boon Love Inspired (Sydney, New South Wales : HarperCollins Publishers, 2021)
An exciting prequel to the True Blue K-9 Unit series Protecting and serving in the Big Apple Her uncle's business practices have put a target on April Reed's back. He's gone into hiding, and April's the only link the drug runners have to him. NYPD K-9 Unit officer Declan Maxwell and his dog Storm will do anything to keep her safe. With danger stalking them, they'll race to save her uncle without losing their lives in the process.
General.
Keywords: Contemporary romance; Electronic books